Bridging Professional Learning and Classroom Practice: Digital Capacity Development among Rural Early Childhood Educators - Nandang Rukanda; Sri Nurhayati; Udeme Samuel Jacob (Institute of Multidisciplinary Research and Community Service, 2026)
Digital transformation in education has expanded opportunities for educator professional learning; however, access to and implementation of digital professional learning opportunities remain uneven across educational contexts. This study investigates patterns of inequality in educators’ access to digital professional learning opportunities and examines how participation is translated into classroom practice in rural early childhood education settings. The study further explores conditions that support or constrain sustained implementation of digital teaching practices. This research employed a qualitative exploratory design involving 13 early childhood educators from multiple institutions in Desa Cijenuk, Kabupaten Bandung Barat. Data were generated through semi-structured interviews, observation, and document study concerning educators’ participation in digital professional learning and implementation experiences. Data were analyzed through iterative thematic interpretation to identify recurring patterns across access, participation, implementation, and perceived support needs. The findings reveal three interrelated patterns. First, access to digital professional learning opportunities was distributed unevenly, with six educators having participated in digital literacy or numeracy professional learning and seven reporting no prior participation. Second, available professional learning frequently emphasized exposure to digital tools rather than sustained pedagogical integration, reducing opportunities for meaningful instructional transformation. Third, participation in professional learning did not automatically translate into continuous classroom implementation. Educators selectively adapted practices based on infrastructural conditions, institutional support, digital confidence, and local teaching realities. At the same time, classroom observations indicated increased child engagement during digitally supported activities but provided no evidence of improved learning outcomes. These findings suggest that inequalities emerge not only in access to professional learning but also in educators’ capacity to enact and sustain digital teaching practices.Keywords: Digital professional learning opportunities, Educator inequality, Digital teaching practices, Early childhood education, Professional learning ecosystems